Rediscovery of Potentilla Supina L. (Rosaceae) In Bangladesh - Hasan, Mohammad Tarikul; Uddin, Mohammad Zashim (Bangladesh Journal of Plant Taxonomy, 2022)
Abstract not available Bangladesh J. Plant Taxon. 29(2): 437-440, 2022 (December)